ANALYSIS OF STUDENT ERRORS BASED ON NEWMAN’S ERROR ANALYSIS (NEA) IN SOLVING COMPLEX PROBLEMS RELATED TO FUNCTION MATERIAL - Dian Elita; Dita Lovianna Purba; Dwita Lestari Saragih; Eka Chirsty Haloho; Budi Halomoan Siregar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Students' errors in solving mathematics problems, particularly on the topic of functions, still frequently occur and need to be analyzed systematically.This study aims to examine students’ errors in solving mathematical problems on function topics based on Newman’s Error Analysis (NEA) procedure. A descriptive qualitative approach was employed in this research. The participants were 23 eleventh-grade students of SMA GKPI Padang Bulan Medan who had previously studied functions. Data were collected through a written test consisting of five word problems and follow-up interviews to explore students’ thinking processes in greater depth. The data were analyzed using Newman’s five stages of error, namely reading, comprehension, transformation, process skills, and encoding. The findings reveal that the most dominant error was encoding error (51.30%), followed by process skill errors (46.96%), transformation errors (39.13%), comprehension errors (34.78%), and reading errors (26.09%). These results indicate that students still encounter difficulties at multiple stages of problem solving, particularly in presenting final answers accurately and carrying out systematic procedures. Therefore, appropriate instructional strategies are needed to enhance students’ conceptual understanding, improve accuracy in calculations, and develop their ability to express final answers clearly and systematically. ABSTRAK Kesalahan siswa dalam menyelesaikan soal matematika khususnya pada materi fungsi masih sering terjadi dan perlu dianalisis secara sistematis. Penelitian ini bertujuan untuk mengkaji kesalahan siswa dalam memecahkan soal matematika pada topik fungsi berdasarkan prosedur Analisis Kesalahan Newman (NEA). Pendekatan kualitatif deskriptif digunakan dalam penelitian ini. Peserta penelitian adalah 23 siswa kelas XI SMA GKPI Padang Bulan Medan yang sebelumnya telah mempelajari fungsi. Data dikumpulkan melalui tes tertulis yang terdiri dari lima soal cerita dan wawancara lanjutan untuk mengeksplorasi proses berpikir siswa secara lebih mendalam. Data dianalisis menggunakan lima tahap kesalahan Newman, yaitu membaca, pemahaman, transformasi, keterampilan proses, dan pengkodean. Temuan menunjukkan bahwa kesalahan yang paling dominan adalah kesalahan pengkodean (51,30%), diikuti oleh kesalahan keterampilan proses (46,96%), kesalahan transformasi (39,13%), kesalahan pemahaman (34,78%), dan kesalahan membaca (26,09%). Hasil ini menunjukkan bahwa siswa masih mengalami kesulitan pada berbagai tahap pemecahan masalah, terutama dalam menyajikan jawaban akhir secara akurat dan melaksanakan prosedur secara sistematis. Oleh karena itu, strategi pengajaran yang tepat diperlukan untuk meningkatkan pemahaman konseptual siswa, meningkatkan akurasi perhitungan, dan mengembangkan kemampuan mereka untuk mengekspresikan jawaban akhir secara jelas dan sistematis.